Creating Research Teacher Community through a Mendeley Training - Ahmad Kailani; Dina Rafidiyah (Comment: an International Journal of Community Development, 2020)
Nowadays, the task of a teacher is not just to teach and evaluate learning outcomes. However, an ideal teacher is those who are able to document and disseminate what occurs in their classroom into a scientific paper or a scientific book. Writing a scientific work is not as easy as writing a short story or novel. There are rules that need to be paid attention by the author, one of them is the rules in citing other works and experts’ opinions. Many scientific papers have been rejected by journal editors because of the citations that do not meet the required author guidelines. To tackle this issue, we conducted a one day training on the use of software reference called “Mendeley” for Senior High School teachers in Barito Kuala Regency. After the training, the participants were able to use Mendeley independently. Even, there was a teacher who succeeded in publishing his scientific article in an online scientific journal.